Synergistic function of N‐P‐Cu containing supermolecular assembly networks in intumescent flame retardant thermoplastic polyurethane. (15th July 2021) - Chen, Kexin; Yang, Dong; Shi, Yongqian; Feng, Yuezhan; Fu, Libi; Liu, Chuan; Chen, Ming; Yang, Fuqiang
Abstract: The design of high‐performance compounded flame retardants based on multielement can be of great significance for reducing the flammability of polymer materials. In this article, a new type of N‐P‐Cu containing supermolecular assembly network (MPCSN) flame retardant was prepared and subsequently added into thermoplastic polyurethane elastomer (TPU)/silicon microencapsulated ammonium polyphosphate (SiAPP) composites. The obtained results indicated that a series of TPU/SiAPP/MPCSN composites exhibited strong adhesions with the TPU matrix. Additionally, the thermal and flame retardant performances of TPU composites were markedly improved after the introduction of different proportions of SiAPP to MPCSN. For example, the peak of heat release rate, the total heat release, the peak of smoke production rate, the total smoke release of the TPU composite containing 7.5 wt% SiAPP and 2.5 wt% MPCSN (TPU/SiAPP3/MPCSN1) remarkably decreased by 68.7%, 52.9%, 52.4%, and 49.4%, respectively, besides the highest LOI value (27.5 vol%) and UL‐94 V‐0 rating, compared with those of pure TPU. The improved flame retardance of the TPU/SiAPP3/MPCSN1 composite was due to the explanations: On one hand, a compact intumescent char effectively protected the TPU matrix from heat and oxygen and retarded the gaseous products permeation into the combustion zone; on the other hand, evolved phosphorus‐containing free radicals captured the H and HO generated from the TPU material. The synergistic effect of SiAPP and MPCSN resulted in strong flame suppression, accompanied by 10.8% and 37.8% reductions in FIGRA and Av‐EHC, respectively. This article offers a facile approach to fabricate highly effective flame‐retardant TPU composites.